2010
DOI: 10.1111/j.1752-4571.2009.00113.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial genetic structure ofAedes aegyptimosquitoes in mainland Southeast Asia

Abstract: Aedes aegypti mosquitoes originated in Africa and are thought to have spread recently to Southeast Asia, where they are the major vector of dengue. Thirteen microsatellite loci were used to determine the genetic population structure of A. aegypti at a hierarchy of spatial scales encompassing 36 sites in Myanmar, Cambodia and Thailand, and two sites in Sri Lanka and Nigeria. Low, but significant, genetic structuring was found at all spatial scales (from 5 to >2000 km) and significant FIS values indicated geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
51
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 73 publications
(104 reference statements)
8
51
2
1
Order By: Relevance
“…Our results confirm the finding of Hlaing et al [5] which reported low but significant genetic structure at all spatial scales within mainland Southeast Asia. Seasonal shifts in allele frequency in the villages may occur when there is a particularly productive water container which leads to a local explosion in mosquito numbers and a genetic bottleneck has changed allele frequencies within this container.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results confirm the finding of Hlaing et al [5] which reported low but significant genetic structure at all spatial scales within mainland Southeast Asia. Seasonal shifts in allele frequency in the villages may occur when there is a particularly productive water container which leads to a local explosion in mosquito numbers and a genetic bottleneck has changed allele frequencies within this container.…”
Section: Discussionsupporting
confidence: 92%
“…aegypti by humans [5], [31]. Movement in the Subdistrict is intensive between some villages in the complex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If Wolbachia does reduce the tendency to participate in long-distance dispersal then it could potentially play a role in population substructure (Hlaing et al 2010) and hence processes like speciation (Craft et al 2010;Drummond et al 2010;Lehrian et al 2010). In an applied context, the capacity to limit dispersal by the artificial introduction of Wolbachia into insect species would be attractive in the case of agricultural pests where dispersal is a critical determinant of invasion success (Liebhold and Tobin 2008).…”
Section: Discussionmentioning
confidence: 98%